Work culture among agro-entrepreneurs - H. M. Thahir, Ira Apriyanti (2008)
Entrepreneurial culture is an expression of positive social attitudes towards commerce at a business level. It can be described as one in which a positive social attitude towards personal enterprise is prevalent, enabling and supporting entrepreneurial activity. It is important to inculcate an agri-entrepreneurial work culture in order to strengthen entrepreneurial capability among the farmers which can lead to sustainable growth in the agribusiness sector and in food production as development of entrepreneurial culture. The general objective of the study is to determine the underlying characteristic of successful agri-entrepreneurs among Farmers Organizaton Authority (FOA) members. Seven hundred and ninety-six (796) farmers who are the members of Farmer Organization and Authority (FOA) were interviewed using a structured questionnaire in order to get the information on their social characteristics and attitudes towards the four states in Northern Region (Perlis, Kedah, Perak dan Pulau Pinang), three states in Eastern Region; (Kelantan, Terengganu and Pahang), two states in Southern Region (Johor and Melaka) and two states in Central Region; ( Selangor and Negeri Sembilan). The samples of the study were selected using a purposive sampling technique. Descriptive analysis, factor analysis and logistic regression were carried out to determine the underlying characteristics of successful agri-entrepreneurs work culture among FO members. The results showed that the majority of the respondents agreed that work culture influenced entrepreneurial behavior in order to be successful as the agri-entrepreneurs. Based on factor analysis, six factors were identified for agri-entrepreneurs to success. These factors are innovative, responsibility and accountability, profit oriented, visionary, work systematic and self confidence. Logistic analysis revealed six factors that have likelihood in influencing the entrepreneurial work culture. These factors were innovative, visionary, work systematic, high formal education, high education in agriculture and high experience in agriculture. All the findings of the study suggest that efforts should be intensified to encourage agri-entrepreneurs with training to focus not only on modern technologies but also on fundamental changes in attitude towards farming as an agribusiness.